Central Bank Financial Strength, Policy Constraints and Inflation - Stella, Peter (IMF Working Papers; Working Paper, 2008)
Central bank financial strength is positively associated with good policy performance. Financially weak central banks generate losses which undermine macroeconomic stability and call into question the credibility of their policies. In assessing central bank financial strength a careful examination of the policy regime and the volatility of the economic environment is necessary. Conventional measures of private enterprise financial strength- profitability and capital-can be very misleading when applied to central banks. The way in which a central bank balance sheet is strengthened matters. Providing the central bank with marketable government debt that can be used to develop a money market that in turn may become the locus of central bank monetary operations serves both to directly strengthen the institution and improve the quality of the environment in which it operates, thereby facilitating the attainment of its ultimate performance objectives.